New challenges in managing user-generated content: the case of Charlie Hebdo - Masip, Pere (Anuario ThinkEPI, 2015)
News organizations have realized that certain types of information and images are more attractive than others to capture the reader´s attention, particularly stories and images about crime and entertainment, among others. At the same time, audiences have become more active, providing eyewitness photos and videos. Newsrooms are flooded with graphic materials submitted by citizens. Along with ease of access may come the publication of extreme content, even when some content may exceed moral boundaries. Publication is often justified on the basis of newsworthiness, freedom of speech, creativity and some kind of technological fatalism. The aim of this short paper is to analyze the coverage by some media outlets of the Charlie Hebdo attack, particularly the use and management of the amateur video of a Paris police officer´s cold-blooded murder. Our results identify some differences depending on the media network (Hallin; Mancini, 2004) of each newspaper. These differences are generally related to questions of ethics, and therefore we emphasize that user-generated content (UGC) must be incorporated into ethical standards of journalism, and journalists should be responsible for their proper implementation.
Keywords: Participatory journalism; Active audience; Coverage; Charlie Hebdo; Journalism ethics; User generated content; UGC.